Prevalence of depression among hypertensive individuals in urban Trivandrum: a cross sectional study - T., Prathibha M.; Varghese, Sara; Dev V., Gokul; J., Jincy (International Journal Of Community Medicine And Public Health, 2017)
Background: People with chronic diseases are more likely to have depression than those without any physical illness. Lack of adherence to treatment, poor compliance to life style modification therapy and lost to follow up are major concerns raised in the management of hypertension among subjects with co-morbid depression. Hence it is very important to explore the epidemiology of depression among hypertensives. Methods: The study was conducted in Medical College health unit area of urban Trivandrum as a cross sectional survey among adults >18 years who were diagnosed to have hypertension. The subjects were interviewed using a semi structured questionnaire to collect the socio-demographic variables and the 9 item Patient Health Questionnaire (PHQ 9) to capture depression. Data from a sample of 432 hypertensive individuals collected were analyzed and Chi square, t test, was done to find the associated factors. Results: Mean age of the study subjects was 62.47 years. Among the study subjects the blood pressure was under control among only 33.8% of the study population. The prevalence of depression was found to be 33.3% (144) with 95% C.I (27.98-39.14). Gender, Socio economic status, marital status, low educational status, regular physical activity, duration of hypertension, uncontrolled BP, were found to be significantly associated with depression. Conclusions: The prevalence of depression among hypertensive individuals is high in this study population. Adequate control of BP along with awareness among primary care physicians in identifying those with hypertension and co-morbid depression is essential.